M1 The british lung foundation online breath test: impact on health-care behaviour. (December 2018) - Elbehairy, AF; Quint, JK; Rogers, J; Laffan, MJ; Polkey, MI; Hopkinson, NS
Abstract : Background: The British Lung Foundation (BLF) online breath test highlighted there is an unmet need associated with breathlessness in the UK. At the end of the test and based on individual responses, subjects were given tailored advice (e.g. life style changes, smoking cessation and weight reduction). A follow up survey aimed to evaluate the impact of taking the test. Methods: 3 65 043 responses were received from the first BLF online breath test ( https://breathtest.blf.org.uk/ ). The current survey was distributed via e mail to individuals who agreed to be contacted after their first test (n=13, 000), roughly one year after the initial survey. Results: 1072 responses were received; 562 remembered taking the first online breath test and were included in the current analysis. Overall characteristics: 76% aged ≥60 years, 9% were smokers, 30% were physically inactive and 69% had body mass index ≥25 kg/m 2 . 40% of this sample reported limiting breathlessness (Medical Research Council dyspnoea score of 3 to 5) and the majority of these (73%) had a diagnosis of a respiratory condition before taking the test. 47% of the subjects reported that taking the online breath test increased their awareness that breathlessness can be a sign of a serious disease. Following the online breath test: 33% reported that they had changed their life style and 20% consulted their general practitioner (GP) about their symptoms. Specifically following their first test, 18% increased their exercise level, 17% changed their diet, 6% successfully quit smoking while 3% had tried to quit but failed. Results following the GP visit are shown in the table 1. Conclusion: These data suggest that applying a simple online breath test can help symptomatic people to consider and address their breathlessness and prompt health promoting behaviour. This in turn could assist in timely diagnosis of conditions causing breathlessness and facilitate providing appropriate care for those who are in need.